ATIM-49 (LTBK-01). AMG 596, A NOVEL ANTI-EGFRVIII BISPECIFIC T CELL ENGAGER (BITE®) MOLECULE FOR THE TREATMENT OF GLIOBLASTOMA (GBM): PLANNED INTERIM ANALYSIS IN RECURRENT GBM (RGBM). (22nd November 2019) - Rosenthal, Mark A; Balana, Carmen; van Linde, Myra E; Sayehli, Cyrus; Fiedler, Walter M; Wermke, Martin; Massard, Christophe; Mellinghoff, Ingo K; Khasraw, Mustafa; Ang, Agnes; Rasmussen, Erik; Kast, Johannes; et al.
Abstract: OBJECTIVES: The class III variant of the epidermal growth factor receptor (EGFRvIII) represents the most common EGFR mutation in GBM. AMG 596 is a bispecific T cell engager (BiTE ® ) molecule designed to engage a patient's own CD3-positive T cells to EGFRvIII-positive tumor antigens. This is the first clinical data readout for AMG 596. METHODS: This phase 1, first-in-human, open-label, sequential dose-escalation/expansion study evaluates continuous intravenous AMG 596 in patients with EGFRvIII-positive GBM or malignant glioma in recurrent (Group 1) or newly diagnosed in maintenance treatment (Group 2) settings. Eligible patients: adults with EGFRvIII-positive GBM or malignant glioma; ≤2 mg/day dexamethasone, ECOG performance status ≤1; life expectancy ≥3 months; and acceptable renal, hematological, and hepatic function. The primary objective evaluates safety and tolerability. Additional assessments include objective response rate per modified Response Assessment in Neuro-Oncology (RANO) Criteria. RESULTS: As of June 2019, 15 rGBM patients (Group 1) were enrolled; 14 patients received ≥1 dose AMG 596. 14/15 (93.3%) patients were evaluable at time of analysis (safety analysis set). Median age was 54.5 years (range, 44–68); 50% were male. Seven patients discontinued for progressive disease (PD). AEs occurred in all patients and were serious in 7/14 (50%). None resulted in discontinuation; two (14.3%) fatal AEs were related to PD. Headache and depressed consciousness (both n=2, 14.3%) were the most common grade ≥3 treatment emergent AEs. In patients with sufficient follow-up to assess response (n=8), 1 (12.5%) achieved partial response, 2 (25%) had stable disease, 4 (50%) had PD at initial scan, and 1 (12.5%) discontinued treatment for PD. Semi-quantitative EGFRvIII expression analysis revealed a median H-score of 115 (range, 8–280). CONCLUSION: This interim analysis suggests a first indication that AMG 596 may be well-tolerated and offer anti-tumor activity in patients with rGBM. Enrollment is ongoing and additional data will be presented. NCT03296696.